How the Entrepreneurial Top Management Team Setup Influences Firm Performance and the Ability to Raise Capital: A Literature Review - Konstantin Maschke; Dodo zu Knyphausen-Aufseß (BuR - Business Research, 2012)
This paper reviews research findings on entrepreneurial top management teams within the last 20 years. It concentrates on team-based management factors and their influence on a new ventures growth and ability to raise capital. This paper integrates recent findings and provides an overview of the current state of research. Moreover, it contributes to the overall topic by proposing five clusters of major team-specific influences, derives determinants of success and failure, and reveals recommendations for further research.
urn:nbn:de:0009-20-33139
Keywords: 650; IPO; entrepreneurial top management teams; literature review; performance; team composition; team demographics; team dynamics; team experience; team leadership; team turnover; venture capital; Unternehmensgründung; Führungskräfte; Arbeitsgruppe; Unternehmenserfolg; Risikokapital; Humankapital; Bibliometrie